2015
DOI: 10.1111/zoj.12335
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution and diversification of an Andean clade of reptiles: combining morphology and DNA sequences of thepallumagroup (Liolaemidae:Phymaturus)

Abstract: Phymaturus comprises 44 species mainly distributed along the south‐west of South America on both sides of the Andes. In this study we present a phylogenetic analysis of Phymaturus of the palluma group, one of its two large clades, including almost all described species. This analysis duplicates the number of in‐group taxa compared with previous contributions. We performed a total‐evidence analysis, combining molecular and morphological characters: sequencing fragments of cytochome b (cytb), 12S, and ND4, for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…Cryptic diversity within Phymaturus is not uncommon, as was revealed recently in Morando et al. () and Lobo, Barrasso, Hibbard, and Basso (), also this phenomenon occurs in its sister genus Liolaemus (see for example studies of Torres‐Pérez et al., ; Medina, Avila, Sites, & Morando, ). In a recent study, González‐Marín, Morando, & Avila (), studied the species of the calcogaster clade ( P. yachanana , P. camilae , P. calcogaster , and P. patagonicus ) using linear and geometric analysis, and presented results that confirm their specific status as they were originally described based on traditional morphology.…”
Section: Introductionsupporting
confidence: 53%
“…Cryptic diversity within Phymaturus is not uncommon, as was revealed recently in Morando et al. () and Lobo, Barrasso, Hibbard, and Basso (), also this phenomenon occurs in its sister genus Liolaemus (see for example studies of Torres‐Pérez et al., ; Medina, Avila, Sites, & Morando, ). In a recent study, González‐Marín, Morando, & Avila (), studied the species of the calcogaster clade ( P. yachanana , P. camilae , P. calcogaster , and P. patagonicus ) using linear and geometric analysis, and presented results that confirm their specific status as they were originally described based on traditional morphology.…”
Section: Introductionsupporting
confidence: 53%
“…Initially, we compiled available sequences from GenBank for four mitochondrial and six nuclear loci from previous published studies on Liolaemidae (Schulte et al 2000;Morando et al 2003;Espinoza et al 2004;Morando et al 2004Morando et al , 2007Avila et al 2007;Victoriano et al 2008;Torres-Pérez et al 2009;Breitman et al 2011Breitman et al , 2012Avila et al 2012;Camargo et al 2012a;Camargo et al 2012b;Fontanella et al 2012a;Fontanella et al 2012b;Vera-Escalona et al 2012;Aguilar et al 2013;Avila et al 2013;Cianferoni et al 2013;Morando et al 2013;Esquerré et al 2014;Olave et al 2014;Avila et al 2015;Breitman et al 2015;Lobo et al 2015;Aguilar et al 2016). We targeted mitochondrial genes cytb, 12S, ND2, and ND4 and nuclear loci B1D, EXPH5, KIF24, MXRA5, PLRL, and PNN.…”
Section: Molecular Samplingmentioning
confidence: 99%
“…3), P. vociferator was observed in volcanic outcrops (Termas de Chillán and road to Aguas Calientes) or Andean vegas (Shangri-la) in sympatry with the lizard Liolaemus chillanensis Müller & Hellmich, 1932 and the snake Tachymenis chilensis (Schlegel, 1837). Some studies have reported the presence of Phymaturus lizards from Termas de Chillán without a formal assignation of species (Lobo & Quinteros 2005b, Eisenberg & Werning 2012, Lobo et al 2016. Lobo & Quinteros (2005b) suggested that this population may correspond to an undescribed species without major conclusions on its identity in a recent taxonomic review of the P. palluma group (Lobo et al 2016) and Eisenberg & Werning (2012) named this population as Phymaturus cf.…”
mentioning
confidence: 99%
“…Some studies have reported the presence of Phymaturus lizards from Termas de Chillán without a formal assignation of species (Lobo & Quinteros 2005b, Eisenberg & Werning 2012, Lobo et al 2016. Lobo & Quinteros (2005b) suggested that this population may correspond to an undescribed species without major conclusions on its identity in a recent taxonomic review of the P. palluma group (Lobo et al 2016) and Eisenberg & Werning (2012) named this population as Phymaturus cf. palluma in a report on the reproduction and biology of these specimens in captivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation